High-Performance Work System, Strategic Flexibility, and Organizational Performance—The Moderating Role of Social Networks - Wang, Yizhi; Cao, Yi; Xi, Nan; Chen, Huitian (Frontiers in Psychology, 2021)
Based on the dynamic capability theory, this research investigated the effect of a high-performance work system on organizational performance, the mediating role of strategic flexibility, and the moderating role of an enterprise’s social network in this relationship. A total of 214 middle and senior managers from 58 Chinese enterprises were invited to participate in this research. The results showed that the high-performance work system is positively correlated with organizational performance and such correlation is partially mediated by strategic flexibility. Results found that the social network of an enterprise negatively moderated the relationship between a high-performance work system and strategic flexibility. However, the social network did not moderate the mediating role of strategic flexibility in high-performance work systems (HPWS) and organizational performance.